Going organic! the how and why of organic foods - Video Education Australasia (Australia : Video Education Australasia, 2000)
Looks at the organic food industry in Australia. Focuses on factors related to the growing popularity of organic foods over the last ten years, the environmental & health benefits of organic farming & organic food, supplying organic food to markets, the role of certifying bodies to guarantee standards and the process of product development such as packaging, marketing and advertising
DVD format
Keywords: Organic farming; Natural foods industry